Amino Acid Medical Foods Provide a High Dietary Acid Load and Increase Urinary Excretion of Renal Net Acid, Calcium, and Magnesium Compared with Glycomacropeptide Medical Foods in Phenylketonuria - Bridget M. Stroup; Emily A. Sawin; Sangita G. Murali; Neil Binkley; Karen E. Hansen; Denise M. Ney (Journal of Nutrition and Metabolism)
Background. Skeletal fragility is a complication of phenylketonuria (PKU). A diet containing amino acids compared with glycomacropeptide reduces bone size and strength in mice. Objective. We tested the hypothesis that amino acid medical foods (AA-MF) provide a high dietary acid load, subsequently increasing urinary excretion of renal net acid, calcium, and magnesium, compared to glycomacropeptide medical foods (GMP-MF). Design. In a crossover design, 8 participants with PKU (16–35 y) provided food records and 24-hr urine samples after consuming a low-Phe diet in combination with AA-MF and GMP-MF for 1–3 wks. We calculated potential renal acid load (PRAL) of AA-MF and GMP-MF and determined bone mineral density (BMD) measurements using dual X-ray absorptiometry. Results. AA-MF provided 1.5–2.5-fold higher PRAL and resulted in 3-fold greater renal net acid excretion compared to GMP-MF (p=0.002). Dietary protein, calcium, and magnesium intake were similar. GMP-MF significantly reduced urinary excretion of calcium by 40% (p=0.012) and magnesium by 30% (p=0.029). Two participants had low BMD-for-age and trabecular bone scores, indicating microarchitectural degradation. Urinary calcium with AA-MF negatively correlated with L1–L4 BMD. Conclusion. Compared to GMP-MF, AA-MF increase dietary acid load, subsequently increasing urinary calcium and magnesium excretion, and likely contributing to skeletal fragility in PKU. The trial was registered at clinicaltrials.gov as NCT01428258.